The tradeoff between water and carbon footprints of Barnett Shale gas. (1st October 2018) - Absar, Syeda Mariya; Boulay, Anne-Marie; Campa, Maria F.; Preston, Benjamin L.; Taylor, Adam
Abstract: Shale gas production is a water and energy-intensive process that has expanded rapidly in the United States in recent years. This study compared the life cycle water consumption and greenhouse gas emissions from hydraulic fracturing in the Barnett region of Texas, located in one of the most drought prone regions of the United States. Four wastewater treatment scenarios were compared for produced water management in the Barnett region. For each scenario, the cradle-to-gate life cycle global warming potential and water scarcity footprint was estimated per mega joule of gas produced. The results show a trade-off between water and carbon impacts, because energy is required for treatment of water. A reduction of 49 percent in total water consumed or a 28 percent reduction in the water scarcity footprint in the shale gas production process can be achieved at a cost of a 38 percent increase in global warming potential, if the wastewater management shifted from business as usual to complete desalination and reuse of produced water. The results are discussed in the context of wastewater management options available in Texas. Graphical abstract: Image 1 Highlights: Computed the life cycle water and carbon footprints of shale gas production. Four scenarios for wastewater management were compared. A lower water scarcity footprint comes at a cost of higher global warming potential. Desalination reduces the water scarcity footprint by 28 percent. Desalination and reuse of produced water increases the carbon footprint by 38 percent.